1997
DOI: 10.1161/01.res.81.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Growth Factor Ligand and Receptor Expression in Response to Altered Blood Flow In Vivo

Abstract: Blood flow and the tractive force shear stress are important determinants of artery caliber, and reduced shear predisposes arteries to intimal thickening and atherosclerosis. The molecular basis for shear-induced changes in artery wall structure is poorly defined. A number of factors associated with normal and pathological artery wall remodeling are induced by shear stress in endothelial cell cultures. These include platelet-derived growth factor (PDGF), a potent mitogen, chemoattractant, and vasoconstrictor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 50 publications
4
75
0
6
Order By: Relevance
“…The proliferative response of SMC leading to neointima formation, however, is probably a pathological response caused by the near-stasis conditions, in that it is not seen in models with 90% flow reduction. 18 Potential factors that could contribute to the proliferative events include hypoxia, accumulation of metabolites, platelet activation, and inflammation, among others. Thus, at least some of the stimuli leading to inward remodeling in the ligation model (eg, SJL/J mice) may be the same as those mediating the remodeling response in flow reduction models with residual forward flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proliferative response of SMC leading to neointima formation, however, is probably a pathological response caused by the near-stasis conditions, in that it is not seen in models with 90% flow reduction. 18 Potential factors that could contribute to the proliferative events include hypoxia, accumulation of metabolites, platelet activation, and inflammation, among others. Thus, at least some of the stimuli leading to inward remodeling in the ligation model (eg, SJL/J mice) may be the same as those mediating the remodeling response in flow reduction models with residual forward flow.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] Our own studies demonstrated that alterations in blood flow also lead to changes in gene expression of platelet-derived growth factor Achain and B-chain, factors known to modulate proliferation and migration of smooth muscle cells (SMC). 18 Preliminary experiments in our laboratory indicated that there is wide qualitative and quantitative variation in the vascular remodeling response of different mouse strains. To provide the basis for a genetic analysis, we subjected 11 different strains of inbred mice to carotid artery ligation for analysis of the remodeling response.…”
mentioning
confidence: 99%
“…25 Vein graft specimens were prepared by using methods described above. Selected vein graft sections were digested in 0.5% pepsin in 0.1N HCl for 30 minutes at 37°C, incubated in 1.5N HCl for 30 minutes at 37°C, washed in 0.1 mol/L borax buffer (pH 8.5) and then in Tris-buffered saline (pH 7.6), 26 and blocked with 10% goat serum in PBS. The sections were incubated with an anti-BrdU antibody (Boehringer Mannheim) at a dilution of 1:20 in 1% BSA-PBS at 37°C for 30 minutes, washed in PBS, incubated with a secondary anti-IgG antibody conjugated with fluorescein (Boehringer Mannheim) at a dilution of 1:20 at 37°C for 30 minutes, and washed in PBS again.…”
Section: Smc Proliferationmentioning
confidence: 99%
“…Endothelial cells are uniquely positioned in the vessel to sense changes in shear stress at the plaque site. Compensation by endothelial cells to restore normal shear stress is achieved by their ability to secrete vasoactive factors such as nitric oxide (NO) (17) or growth factors such as platelet-derived growth factor (18)(19)(20). Support for a critical role of endothelial cells includes the report by Tronc et al (21) that blocking NO formation with L-nitroarginine inhibited flow-dependent remodelling in rabbits by approximately 70% and data for diminished remodelling in the endothelial NO synthase (eNOS) knockout mouse (18).…”
Section: Three Biological Laws Define Vascular Remodellingmentioning
confidence: 99%
“…Compensation by endothelial cells to restore normal shear stress is achieved by their ability to secrete vasoactive factors such as nitric oxide (NO) (17) or growth factors such as platelet-derived growth factor (18)(19)(20). Support for a critical role of endothelial cells includes the report by Tronc et al (21) that blocking NO formation with L-nitroarginine inhibited flow-dependent remodelling in rabbits by approximately 70% and data for diminished remodelling in the endothelial NO synthase (eNOS) knockout mouse (18). A recent paper by Stone et al (3) showed that in the presence of high shear stress (τ greater than 38 dynes/cm 2 ), atherosclerotic arteries remodelled by decreasing plaque area and increasing lumen without changes in vessel size measured by r ext .…”
Section: Three Biological Laws Define Vascular Remodellingmentioning
confidence: 99%